Cis-acting regulatory elements controlling temporal and organ-specific activity of nopaline synthase promoter. - Ha, S B (Nucleic Acids Res, 1989)
Regulatory elements controlling temporal and organ-specific expression of the nopaline (nos) gene were identified by analyzing deletion mutants of the promoter. As observed in cultured cells, the TATA box element was required for efficient promoter function and the 29 bp upstream promoter region between -130 and -101 was necessary for the nos promoter activity in various vegetative organs. This 29 bp region includes ten nucleotides of a potential Z-DNA-forming sequence (Z element) and eight nucleotides of a repeated element (b element). Duplication of b elements significantly enhanced the promoter strength, revealing the importance of the element in all plant organs. Unlike the results in the cultured cells, however, deletion of the b element or CCAAT box region completely inactivated the promoter function in regenerated organs. Therefore, it appears that transcription initiation is more tightly controlled in differentiated plant cells than in cultured cells. IMAGES: